Tower Crane Productivity Analysis on Apartment Development Projects - Maddeppungeng, Andi; Asyiah, Siti; Intari, Dwi Esti; Setiawati, Dwi Novi; Ujianto, Rifky; Gibran, Achmad (Jurnal Fondasi, 2024)
The development of infrastructure technology in Indonesia has seen a significant and rapid growth. Along with this advancement, the number of construction projects has also increased, thanks to the availability of advanced tools and equipment. In construction projects, it is crucial to adhere to the agreed-upon design and complete the work within the designated timeframe. This ensures that there are no setbacks or delays in the construction process. The objective of this study is to determine the types of Tower Crane heavy equipment used, assess the productivity of the Tower Cranes, and identify the optimal positioning for the Tower Cranes. This research was conducted on the Juanda-Bekasi Transpark Area Development Project. Based on the analysis results, it was found that the project utilizes three Tower Cranes of the C7030-12T type. Tower Crane 1 exhibited the highest productivity, with a value of 3326.3881 kg/hour. Tower Crane 3 had a productivity value of 3286.3825 kg/hour, while Tower Crane 2 had a productivity value of 2069.2752 kg/hour. The highest productivity value for Tower Crane 1 was recorded on September 28, at 4662.57 kg/hour. For Tower Crane 2, the highest productivity value was observed at 2919.52 kg/hour. Tower Crane 3 achieved its highest productivity value on September 8, at 5341.45 kg/hour. Among the three simulations conducted in this study, the optimal configuration for Tower Crane placement was obtained in the second simulation, which involved using two Tower Cranes.